Modern diagnostics of nonalcoholic fatty liver disease: noninvasive research methods - Palibroda, N. M. (Regulatory Mechanisms in Biosystems, 2016)
Nonalcoholic fatty liver disease (NAFLD) is increasingly recognized as the most common cause of chronic liver disease worldwide. NAFLD represents a wide spectrum of conditions, ranging from simple benign steatosis to nonalcoholic steatohepatitis, which sometimes progresses to cirrhosis and hepatocellular carcinoma. The pivotal issue in the management of patients with NAFLD is the diagnosis of steatohepatitis and fibrosis at an early stage. In this review we present recent data on nonalcoholic fatty liver disease evaluation. Although liver biopsy is regarded as the gold standard for assessment of hepatic steatosis and steatohepatitis, its use has several limitations, including the potential risk of sampling errors, intra- and interobserver variability, invasiveness and the stress it causes to patients, the high cost and the potential for complications. In this review a simple and reliable non-invasive alternative with indicated sensitivity and specificity is described. Non-invasive markers should aim ; in primary care settings, to identify the risk of developing NAFLD among individuals with increased metabolic risk; in secondary and tertiary care settings, to identify those with a worse prognosis, e.g. severe steatohepatitis; monitor disease progression; predict response to therapeutic interventions. Achieving these objectives could reduce the need for liver biopsy. Thus, according to the natural history of NAFLD, all patients with a low risk of developing advanced disease, eventually diagnosed by one of above non-invasive parameters, could be referred to primary care, whereas subjects at high risk of developing advanced disease should be sent to specialists for the evaluation of the degree of fibrosis and the choice of specific management. According to the Clinical Practice Guidelines for the management of NAFLD, ultrasound is the preferred first-line diagnostic procedure for imaging of NAFLD, as it provides additional diagnostic information. Whenever imaging tools are not available or feasible (e.g. large epidemiological studies), serum biomarkers and scores are an acceptable alternative for the diagnosis of steatosis. The combination of biomarkers/scores and transient elastography might confer additional diagnostic accuracy. At the same time, the identification of advanced fibrosis or cirrhosis by serum biomarkers/scores and/or elastography is less accurate and needs to be confirmed by liver biopsy, according to the clinical context. Аlthough there are a range of controversial issues regarding the use of non-invasive methods for the assessment of NAFLD, these methods are being actively developed, researched and introduced into clinical practice as an equivalent and substitute for liver biopsy.